Nutritional Benefits of Black Soldier Fly Larvae Oil in Animal Feed - Rudy Agung Nugroho; Retno Aryani; Esti Handayani Hardi; Hetty Manurung; Rudianto Rudianto (Universitas Muhammadiyah Surakarta, 2024)
Black Soldier Fly Larvae (BSFL) oil is currently an insect oil that potentially replaces fish oils in animal feed. However, there are limited information on its benefits and nutritional comparison of BSLF oil to fish oil. Present study was to evaluate the benefits of BSFL oil in animal feed and compare the BSFL to Fish oil. Collected data of BSFL oil in the animal feed and its physiological effects was obtained from several articles of reputable journal and compiled into a table. Meanwhile, BSFL was reared and extract their oil to determine the fatty acid composition and compare to fish oil. The current study indicated that BSFL oil can be used in various animal feeds, such as aquafeed, broiler feed, and pets. The BSFL oil which is included in the feed showed an improvement in growth and other physiological responses of animals. Meanwhile, in comparison to fish oil, BSFL oil has a similar composition of fatty acids such as Omega 3 and Omega 6. Eicosapentaenoic acid (EPA; 20:5n3) is detected in the BSFL oil, though the quantity is much lower than in fish oil. Further, the BSFL oil also contains lauric acid. In conclusion, BSFL oil can be an alternative feed ingredient to substitute fish oil and has beneficial to the growth and physiological responses of the animal.